PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIK YAMAHA MIO M3 125 PADA DEALER MATARAM SAKTI DI SEMARANG - Rendi Hermawan; Apriatni EP (Jurnal Ilmu Administrasi Bisnis, 2017)
Purchasing decission is the goal that every company have to reach. As the new product, Yamaha Mio M3 125 Blue Core should to concern every factors which can drive the purchasing decission. The type of research is explanotory research with 76 respondents which calculated using purposive sampling technique. Instrument data collection technique is by questionnaire and interview. Data were analyzed using liner regression analysis by SPSS 23 For Windows.This research concludes that product has a positive and significant influence on puchasing decission. Product explained the purchasing decission at 11,4%. Price has a positive and significant influence on puchasing decission. Price explained the purchasing decission at 4,2%. Promotion has a positive and significant influence on puchasing decission. Promotion explained the purchasing decission at 18,8%. those variabels can explain 25,6% variabel purchase decision.Based on the results of this concluded that consumer perception of product quality, price, and promotion are in good category. Meanwhile, purchasing decisions Yamaha Mio M3 is high. So companies are advised to keep creating good products and competitive so as to attract the hearts of consumers. In addition, the company also can fix the things that can increase the positive perception of consumers. Among them are to improve product quality and increase promotional activities more interesting.